Temporal variation and spatial distribution of Euschistus heros (Hemiptera: Pentatomidae) during the soybean grain formation period (Research, Society and Development, 2022)
The neotropical brown stink bug Euschistus heros (Hemiptera: Pentatomidae) is one of the most important pests in soybean and knowledge of its distribution is necessary to determine the moment of control and enable the appropriate use of strategies to avoid production losses. This research aimed to study the temporal variation and the spatial distribution of E. heros in soybean. The study was carried out in an area of 6600 m2 of soybean, with 60 plots of 100 m2 each, with two sampling points/plot being evaluated weekly by the beat cloth method to count nymphs and adults. The evaluations occurred from fruiting (R3) to physiological maturation (R8). The data were subjected to dispersion indices (variance/mean ratio, Morisita index, and exponent k), theoretical frequency distributions (Poisson, negative binomial, and positive binomial), and spatial analysis by inverse distance weighting (IDW). This study demonstrated the infestation of E. heros throughout the evaluation period, and the dispersion indices showed the trend of nymph aggregation and the sum of nymphs and adults (total population). However, adults tended towards a moderate to uniform aggregation. Theoretical frequency distributions for nymphs and total population indicated randomness at the beginning of the infestation, tending to aggregation from R5 onwards. Aggregation is confirmed in adults, but the population tended towards uniformity at the end of the cycle. The use of the IDW method is an important tool for the rational management of the neotropical brown stink bug in the soybean crop.